MEDIA KOMIK MATEMATIKA DIGITAL UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI DAN RESILIENSI MATEMATIS SISWA - Atika Hidayah; Netriwati; Fraulein Intan Suri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to develop digital mathematics comic media to improve students' mathematical representation and resilience skills. The research method used is Research and Development (R&D) by adopting the DDD-E (Decide, Design, Develop, and Evaluate) model. The results of this development research are in the form of digital mathematics comic media on the material of lines and angles that can be accessed via gadgets online. The level of product validation is obtained from the assessment of the expert team, namely material validation 4.43 with the category